Negociações e invenções cotidianas como potências de um currículo para uma vida bonita - Prezotti, Letícia Regina Silva Souza (2015)
This writing is a test of the power of knowledge networks and practices of elementary school students from public schools in the city of Guarapari / ES in different spacestimes that are daily experienced by producing knowledge when political, social and cultural network wires are tissued. It discusses. It discusses the political practices which are invented at schools by their practice subjects, students, teachers, whose inside and outside relationships bring the possibilities of feeling, thinking and doing the senses and meanings production education. It dialogues with the studies of "thinking with each other", "the arts / ways of doing" from Certeau, "the conversations and experiences" from Larrosa, the "culture of between place" from Bhabha, "the power of accomplished resume" from Ferraço, the "dentrofora" from Alves, the "curriculum for social emancipation", from Oliveira, "good meetings" presented by Carvalho, among others, which intertwine to believe in the power of everyday knowledge and actions conceived and practiced in its implications for the subjectivity processes of subjects practitioners. It focus on methodological approach of the knowledge network, conversations, narrativesimages of maps which accompany the utterances, the looks and the ways that research goes through the powerful translation of hybrid identities that move the learning process. It gives the idea of the existence of politicalpractices that produce the idea of experiencecurriculum and tradingcurriculum.